Heavy metal accumulation in small terrestrial rodents infected by cestodes or nematodes - Jankovská, I; Langrová, I; Bejcek, V; Miholová, D; Vadlejch, J; Petrtyl, M (Parasite (Paris, France), 2008)
The aim of the present study was to assess whether there is a difference in accumulation of heavy metal ions (Cd, Cr, Cu, Mn, Ni, Pb and Zn) in hosts (small mammals) infected by cestode parasites when compared to those without cestode infection. The abundance of gastrointestinal parasites and bioaccumulation of heavy metals in host livers and kidneys were measured. Contents of heavy metals in hosts were determined by ICP OES method. The hosts with cestode infection (Paranoplocephala sp.) had lower contents of heavy metals in their livers and kidneys compared to hosts with nematode infection (Mastophorus muris). The content of Pb, Cd, Cr, Cu and Ni was higher in kidneys than in livers, in both (cestode and nematode infected) rodents while the content of Mn was higher in livers. Content of Zn was similar. The content of heavy metals in host was decreasing with the increasing abundance of cestodes (Paranoplocephalo sp.). Species-response models to particular heavy metals are presented.
Keywords: Liver; Metals, Heavy; Nematode Infections; játra; mužské pohlaví; Rodent Diseases; cestodózy; nematodózy; těžké kovy; Nematoda; nemoci hlodavců; ženské pohlaví; Rodentia; zvířata; hlodavci; ledviny; Species Specificity; Cestoda; hlístice; druhová specificita; Kidney; Cestode Infections; Female; Male; Animals